Understanding terrorism challenges, perspectives, and issues - Martin, Gus (SAGE, 2021)
Understanding Terrorism: Challenges, Perspectives, and Issues offers a comprehensive, interdisciplinary exploration of domestic and international terrorism that helps students develop the knowledge and skills needed to critically assess the underlying causes of modern terrorist violence.